DISEMINIASI TEKNOLOGI PUPUK ORGANIK DALAM USAHA TANI KONSERVASI DI KAMPUNG WALAL DISTRIK SALAWATI - Soekamto, Mira Herawati; Tabara, Reijeng; Ohorella, Syarif; Irnawati, Irnawati (Gapenas Publisher, 2025)
The impact of the use of chemical fertilizers and pesticides has had an impact on the decline in soil fertility. while on the other hand the need for food continues to increase along with the increase in population. Conservation farming efforts with the use of organic fertilizers are a solution to increase soil fertility and quality. Approach efforts to change farmers' mindsets to use organic fertilizers need to be carried out by carrying out counseling, training, mentoring and creating sample plots for plant cultivation. The results of the activity showed an increase in farmers' knowledge by 72% after participating in the dissemination program, as shown through pre-test and post-test evaluations. In addition, farmers began to adopt the use of organic fertilizers on their agricultural land, resulting in increased crop productivity and improved soil quality. This success reinforces the importance of organic fertilizer technology as a solution in maintaining environmental sustainability and supporting farmer independence in the area. With significant results, this approach is recommended to be replicated in other areas with similar conditions.